Image Preprocessing and Background Removal with Pixel-level Analysis - Kittappa, Thiagarajan; Mageshwaran, D.R.; Mithun, S.; Charmi, T. Muni; Anburaja, Anish; Snehal, S. Mrithul (Migration Letters, 2023)
The problem of exact background removal stands as a cornerstone challenge with broad consequences in the ever-evolving field of image processing. The proposed research presents a novel method to overcome this problem by utilizing pixel-level analysis and sophisticated algorithms. The proposed technology, significantly improves the accuracy and effectiveness of background removal by accurately identifying and isolating background features. Also, it is having an impact on industries including computer vision, e-commerce, and content development. Recent modern deep learning algorithms are combined with pixel-by-pixel classification jointly in proposed approach, resulting in a notable improvement when compared to traditional methods. The proposed method demonstrates its flexibility across various image kinds and levels of complexity.